Ablation mechanism and morphology evolution of the HfC-SiC coating for C/C composites deposited by supersonic atmospheric plasma spraying. (14th August 2019) - Yang, Yang; Li, Kezhi; Zhao, Chun
HfC-SiC protective coating was deposited on the surface of SiC-coated carbon/carbon composites by supersonic atmospheric plasma spraying due to the high arc temperature and the efficient deposition rate. The morphology and microstructure of the HfC-SiC coating were analyzed by X-ray diffraction and scanning electron microscopy. The results showed that Hf and Si elements distributed uniformly in the coating and the coating was dense without crack. Ablation resistance test was processed by oxyacetylene torch. During the ablation process, the sintering rate of HfO2 was slow, and more oxygen diffused into the internal coating, which caused the oxidation of the internal coating and damaged the structure of internal coating in the ablation center region. In addition, during cooling process, a new phase HfSiO4 was generated by the reaction between HfO2 and SiO2, which acted as a pinning agent to prevent the further expansion of the crack.